Cord blood and peripheral nucleated red blood cells levels in term asphyxiated and non-asphyxiated new borns and neonatal outcome: a comparative study - Chauhan, Mukul; Jaipal, Munna Lal; Bisht, Surender Singh; Tyagi, Amita (International Journal of Contemporary Pediatrics, 2021)
Background: Perinatal asphyxia can cause severe hypoxic-ischemic damages in the organs and causes severe long-term consequences. It has recently been suggested that the increase in NRBC count in the umbilical vein of newborns can be considered a sign of birth asphyxia. The aim of the study was to evaluate the role of cord blood nucleated RBC count as a marker for presence and severity of birth asphyxia. Methods: This prospective observational comparative study was conducted among 30 asphyxiated (case) and 30 non-asphyxiated newborns (control) in Swami Dayanand Hospital. Number of nucleated red blood cells in cord blood and peripheral blood were counted per 100 leukocytes in smears in cases and control. Maternal parameters and neonate characteristics were recorded in a proforma. Results: NRBC count increased in cord blood during the first few hours of life in perinatal asphyxia (10.79±9.58) as compared with the healthy control subjects (4.03±2.87, p=0.002). Significant positive correlation of C-NRBC and P-NRBC with NICU stay (r=0.921, p<0.0001 and r=0.698, p<0.0001 respectively). Nucleated RBC count more than 18 can be used as predictor of abnormal neurological outcome with sensitivity 100% and specificity of 93.1%. The cord blood NRBC >3/100 WBC has sensitivity of 92% and specificity of 77.8% in predicting birth asphyxia. Conclusions: Nucleated RBC count can be used as surrogate marker for birth asphyxia. It has significant positive correlation with severity of hypoxic ischemic encephalopathy, duration of NICU stay and duration of O2 requirement.